Survival of anti-Clostridium difficile bovine immunoglobulin concentrate in the human gastrointestinal tract. - Kelly, C P (1997)
To be therapeutically active, oral hyperimmune bovine immunoglobulin concentrate (BIC) must survive its passage through the intestinal tract. This led us to study the gastrointestinal stability of orally administered BIC directed against Clostridium difficile toxins (BIC-C. difficile). BIC-C. difficile was stable at neutral pH in vitro but was degraded at low pH, particularly in the presence of pepsin. Healthy volunteers (n = 6) took BIC-C. difficile (45 or 8 g) as a single oral dose. Total bovine immunoglobulin G (IgG) and specific anti-C. difficile IgG were measured in the stool. BIC was given under the following conditions: in the fasting state, in the fed state, with antacid, during omeprazole therapy, or in enteric capsules (released at pH > 6). The mean fecal bovine IgG content of 3-day stool collections was similar in the fasting (536 mg; 3.8% of the ingested dose of BIC), fed (221 mg; 1.6%), and antacid (381 mg; 2.7%) groups. Omeprazole therapy was associated with increased fecal bovine IgG levels (1253 mg; 8.8%), but this difference did not reach statistical significance (P = 0.07). Administration of 8 g of BIC-C. difficile in enteric capsules resulted in substantially higher fecal bovine IgG levels (1,124 mg; 32.7% of the oral dose) than those obtained after administration of nonencapsulated BIC (22 MG; 0.6%; P = 0.004). An inverse relationship was noted between intestinal transit time and fecal bovine IgG content (R = 0.83; P = 0.04 [data from omeprazole group]). Filtrates of stool samples collected after oral administration of BIC-C. difficile neutralized the cytotoxicity of C. difficile toxins A and B, whereas control stool filtrates did not. Bovine colostral IgG undergoes partial degradation in the intestinal tract. Exposure to acidic gastric secretions and prolonged colonic transit may both contribute to IgG degradation. Nonetheless, humans taking BIC-C. difficile orally have neutralizing antitoxin activity in their stool.